PEMANFAATAN KANTIN KEJUJURAN SEBAGAI MEDIA PEMBENTUKAN KARAKTER JUJUR PESERTA DIDIK DI SD NEGERI CIKANDE 1 - Supyadi, Muhammad Rifki; Taufik, M.; Firdaus, Firdaus (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to describe the use of an honesty canteen as a medium for fostering students’ honesty character in elementary school. The research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, and analyzed through data collection, reduction, presentation, and conclusion drawing. The findings showed that the planning and implementation of the honesty canteen program at SD Negeri Cikande 1 were carried out effectively as an effort to develop students’ honesty character. The daily operation of the honesty canteen ran smoothly, with the responsible teacher managing preparation, supervision, closing, and daily financial calculations consistently. The results also indicated significant development in students’ honesty character. Honesty was not only understood as a concept but had become a habit and part of the school culture. Students demonstrated strong honesty values and were able to remind and encourage their peers to behave honestly. In conclusion, the honesty canteen serves as an effective medium for strengthening students’ honesty character in elementary education.